The Development and Validation of an Italian Short Form of the Adolescent Friendship Attachment Scale. (October 2014) - Baiocco, Roberto; Pallini, Susanna; Santamaria, Federica
The aim of the present study is to validate a short form of the Adolescent Friendship Attachment Scale that evaluates best friend's attachment considering three styles: Secure, Anxious, and Avoidant. The scale demonstrated adequate internal consistency. Confirmatory factor analysis confirmed the three-factor structure as found in the long form.